2007
DOI: 10.1007/s10750-007-0799-y
|View full text |Cite
|
Sign up to set email alerts
|

Palaeolimnological evidence for the independent evolution of neighbouring terminal lakes, the Murray Darling Basin, Australia

Abstract: The estuary of the lower River Murray features a complex mosaic of lakes, coastal lagoons and interconnecting channels. The waters of these wetlands are degraded as a result of river regulation, water abstraction, salinisation, sedimentation and the recent constriction of the River mouth. Palaeolimnologial analysis of sediment cores in two wetlands reveals that salinity in the large terminal Lake Alexandrina was only moderately influenced by tidal inflow, particularly over the past ca. 2000 years. It is now la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
93
1
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(102 citation statements)
references
References 21 publications
5
93
1
3
Order By: Relevance
“…7). This agrees with previous descriptions of Grammatophora marina and Opephora pacifica which have been classified as marine taxa (Vos and de Wolf 1993;Fluin et al 2007). Planothidium hauckianium agg.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…7). This agrees with previous descriptions of Grammatophora marina and Opephora pacifica which have been classified as marine taxa (Vos and de Wolf 1993;Fluin et al 2007). Planothidium hauckianium agg.…”
Section: Discussionsupporting
confidence: 93%
“…Whilst most of these more abundant taxa have been previously described as 'brackish-marine' taxa, this study permits a finer scale discrimination of their salinity preferences. For example, Cocconeis placentula has previously been identified as a brackish, shallow water species (Hodgson et al 1996;Fluin et al 2007), and this study is consistent with these observations (i.e. it was most abundant in brackish conditions, 5-30 ppt, Fig.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This lead to calls for the dedication of 700 GL of river water into the system to save the Coorong and adjacent lakes (Gell 2010). Palaeolimnological evidence from cores taken the length of the Coorong revealed it to have a subsaline history with little direct contribution from the river (Fluin et al 2007), as revealed by very low levels of the river plankter Aulacoseira granulata (Figure 3). In fact, it was highly reliant on freshwater contributions from Salt Creek.…”
Section: Assessment Of Natural Ecological Charactermentioning
confidence: 99%